THE ROLE OF OXIDATIVE STRESS BIOMARKERS IN ANIMAL HEALTH, TOXICOLOGY, AND ENVIRONMENTAL MONITORING - Tiba Najim Hasan (International Journal of Science and Research Archive, 2026)
The oxidative stress biomarkers have gained significance in veterinary medicine, animal production, toxicology and environmental biomonitoring because of their link between redox imbalance and clinically as well as ecologically relevant results. RONS are produced during metabolism, immune defence, reproduction, growth and adaptation but excess production or a lack of antioxidants can lead to damage of lipids, proteins, DNA, mitochondria and cellular membranes. This review includes an integrated biomarker framework, practical interpretation criteria and original explanatory diagrams which detail the use of oxidative stress markers within animal health, toxicological evaluation and environmental monitoring, incorporating a One Health perspective. The biomarkers reviewed are those involved in lipid peroxidation (malondialdehyde), antioxidants (superoxide dismutase, catalase, glutathione peroxidase, and glutathione S-transferase), and molecular damage markers (protein carbonyls and 8-hydroxy-2'-deoxyguanosine). The oxidative stress biomarkers reviewed in this report are not diagnostic biomarkers of their own, but rather are indicators of early warning and should be combined with pathology, performance indicators, contaminant data and longitudinal surveillance.